"A Degree in What?" Revisited: A Response to Psychological Hermeneutics for Biblical Themes and Texts (Ellens, 2012) - Kille, D. Andrew (Pastoral psychology, 2015)
J. Harold Ellens's Psychological Hermeneutics for Biblical Themes and Texts (Ellens 2012) offers a comprehensive survey of the recent development of psychological biblical criticism and the role played in that development by Wayne G. Rollins. The field still displays a persistent lack of coherence, comprising many different methods and approaches. Hal Childs's introduction to the work of Wolfgang Giegrich in this volume suggests a possible way to comprehend that diversity and what holds it together.